Provision of human services by third parties and their effects on the public values: A review of the empirical literature - Cunill-Grau, Nuria; Leyton Navarro, Cristian (Revista Estudios de Políticas Públicas, 2021)
This article explores the evidence on the provision of human services by third parties and their effects on public values such as equity, quality of services, social participation, accountability, and citizenship rights in general. It considers the types of social actors involved and types of institutional arrangements relative to the State. Positive or negative effects identified in different dimensions of the public values tend to depend on the type of provider and the institutional arrangements that define its relationship with the State. However, the most salient finding is that the existing empirical studies, with few exceptions, propose to focus on effects on the efficiency of services rather than look more deeply into the matter of the public values. This study stresses the need for further comparative research of the public domain that will allow researchers to discern who can make better contributions in its various dimensions. It also identifies new avenues of research.